The Grimm Conclusion - Gidwitz, Adam; Grimm, Jacob 1785-1863.; Grimm, Wilhelm, 1786-1859. (New York, New York : Dutton Children's Books, an imprint of Penguin Group (USA) Inc., 2013)
"Sister and brother Jorinda and Joringel fight to keep their promise to stay together throughout a new series of gruesome, twisted, Grimm-inspired stories"--
Keywords: Fairy tales; Fairy tales; Characters in literature -- Fiction; Brothers and sisters -- Fiction; Adventure and adventurers -- Fiction; Humorous Stories